Regulation of 11β-hydroxysteroid dehydrogenase type 1 following caloric restriction and re-feeding is species dependent. (1st October 2017) - Loerz, Christine; Staab-Weijnitz, Claudia; Huebbe, Patricia; Giller, Katrin; Metges, Cornelia; Rimbach, Gerald; Maser, Edmund
Abstract: Evidence in the current literature suggests that expression and activity of 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1), a key regulatory enzyme in glucocorticoid metabolism, is elevated in the liver and reduced in visceral adipose tissue and skeletal muscle following caloric restriction (CR). In order to investigate the influence of CR on 11β-HSD1 in more detail, we assessed expression and activity of 11β-HSD1 in several tissues in two independent CR and re-feeding animal models. Levels and activity of 11β-HSD1 after CR and re-feeding were measured [mouse liver and pig liver, pig visceral adipose tissue and pig skeletal muscle] using semi-quantitative RT-PCR, Western Blot analysis, and HPLC. After CR, no significant difference on mRNA levels was detected in mouse liver. But 11β-HSD1 mRNA expression was upregulated after subsequent re-feeding. In contrast, 11β-HSD1 protein expression after CR was significantly up-regulated, while no difference was detected after re-feeding. Interestingly, upregulation of protein after CR (1.4-fold) was lower than the increase in enzymatic activity (2.6-fold). Furthermore, while no difference was observed in protein levels after two weeks re-feeding, 11β-HSD1 activity increased 2.5-fold. In pig tissues neither 11β-HSD1 mRNA levels, protein expression or enzyme activity were influenced after CR and re-feeding. Overall, the results demonstrate species-dependent differences in regulation of 11β-HSD1 following CR and suggest the presence of an additional regulation step for 11β-HSD1 activity in mouse liver. Highlights: Diet induces changes in expression and activity of 11β-HSD1 in a mouse model. No regulation of 11β-HSD1 by dietary changes were observed in a porcine model. Regulation of 11β-HSD1 during caloric restriction/re-feeding is species-dependent.